RANGKAIAN KASUS CEDERA OTAK PENETRASI: PATOMEKANISME, IMPLIKASI KLINIS, DAN PENATALAKSANAAN DENGAN SUMBER DAYA TERBATAS - Andini, Putri; Yugo, Mohammad Reynalzi; Yunus, Reyhan Eddy; Prawiroharjo, Pukovisa (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Penetrating brain injury differs markedly from blunt injury in dural tears and the transmission of kinetic energy to the surrounding structures along the penetrating tract. Unique clinical characteristics of penetrating brain injury (PBI) certainly require a case-by-case approach, however there are some principles that can be applied in almost every case and need to be considered to improve the outcomes. We present three cases of PBI with different mechanisms and outcomes. Two of the cases presented with non-missile PBI, while the third case presented with missile PBI. We also present a review of current literature highlighting various pathomechanisms, clinical implications and key approaches in managing PBI, particularly in resource-limited settings.